Respecting Animals in Order to Respect People - Georges Chapouthier (Universitat Autonoma de Barcelona. Facultat de Dret, 2020)
Human intelligence has two facets: a quantitative facet, stemming from the extreme complexity of the human brain, and a more qualitative facet, linked to the plastic and juvenile nature of the brain. The latter is what allows us to switch so easily between good and evil, thus making education a necessity for maintaining morality in such a mercurial species. However, in order to achieve its ends, education cannot be satisfied with appealing to imperatives that concern only human beings. To achieve a better morality, we must also know how to respect other sentient beings, i.e. animals. Learning to respect someone weaker than oneself is the first step in showing respect. One must therefore learn to respect animals in order ultimately to respect humans.